Patient with Severe Skeletal Class II Malocclusion: Double Jaw Surgery with Multipiece Le Fort I - Merve Altay Burgaz; Feyza Eraydın; Simge Diren Esener; Ersin Ülkür (Galenos Yayinevi, 2018)
A 22-year-old woman with severe skeletal Class II malocclusion was referred to our clinic. A clinical examination revealed a convex soft tissue profile and increased teeth and gingiva exposure both while smiling and in the natural rest position. She had Class II molar and canine relationship with increased overjet, moderate crowding in both upper and lower jaws, and proclined upper and lower incisors. Skeletally, she showed transverse maxillary deficiency, maxillary vertical excess, and mandibular retrognathia. We planned orthodontic- orthognathic surgery with multipiece Le Fort I osteotomy and bilateral sagittal split osteotomy (BSSO) to achieve ideal occlusion, stability, and facial esthetics. During orthodontic decompensation to relieve the crowding and to gain an ideal incisor inclination, four bicuspid extractions were performed. Because we used continuous mechanics, at the end of the decompensation period, we cut the maxillary arch wire distal to the lateral incisors into three pieces and waited for 3 months for vertical and transversal dental relapse. During the double jaw surgical procedure, the maxilla expanded and impacted with multisegmented Le Fort I osteotomy and the mandible advanced with BSSO. After the orthodontic and orthognathic surgical treatment, the skeletal and dental imbalance was corrected, and functional occlusion and dental and skeletal Class I relationship were achieved. The treatment results were stable at the 1-year follow-up.